PENGEMBANGAN KEMAMPUAN BERBAHASA ARAB MAHASISWA DALAM PRAKTIK PENGALAMAN LAPANGAN DI MADRASAH ALIYAH: STUDI PENGEMBANGAN KEMAMPUAN BERBAHASA ARAB MAHASISWA DALAM PRAKTIK PENGALAMAN LAPANGAN - Umar; Laely Syaudah; Aceng Cahyani; Abdul Rosyid; Ajironi; Sugito; Yusron Alhariqazhar; Ibnu Hanif Almadani; Mustaji; Agus ikhsannudin; Asep Parida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Teaching Practice Program (PPL) is an essential stage in developing pre-service teachers’ professional competence. This study aims to describe the challenges faced by students of the Arabic Language Education Department of IAI AL-AZIS during their PPL at Ma’had Al-Zaytun Islamic Senior High School and to explore the strategies they used to overcome them. This research employed a qualitative descriptive approach using data derived from student reports, field observations, and reflections. The results indicate that the main challenges include classroom management, limited preparation time, adaptation to the school environment, and choosing appropriate Arabic teaching methods. The strategies adopted involved collaboration with supervising teachers, creative use of instructional media, reflective practice, and implementation of hiwār and istimā‘ methods. The PPL experience was proven to be an effective medium to develop students’ pedagogical, professional, and social competence as future Arabic language teachers.